Wonder Woman Omnibus - Pérez, George 1954-2022; Wein, Len 1948-2017; Potter, Greg (DC Comics, 2015)
"One of the most popular artists working in comics over the last 30 years, George Pérez's resume contains a who's-who of the most popular characters in comics. From his co-creation, with Marv Wolfman, of THE NEW TEEN TITANS in the 80s and his work on CRISIS ON INFINITE EARTHS and WONDER WOMAN to his mega-successful JLA/AVENGERS, George's work has thrilled comics fans for over 3 decades.
Keywords: Wonder Woman (Fictitious character) -- Comic books, strips, etc; Wonder Woman -- Fiktive Gestalt; Superhero comic books, strips, etc; Graphic novels; Women superheroes -- Comic books, strips, etc; Superheldin; Comic